Task Construal Influences Estimations of the Environment - Keric, Vjeran; Sebanz, Natalie (Frontiers in Human Neuroscience, 2021)
People’s characteristics can affect their perception of the physical environment, and the judgments and estimates they make about their surroundings. Estimates of the environment change based on observers’ metabolic state, physical properties, and the potential effort they would need to exert for a certain action. The functional role of such scaling is to provide agents with information on possible actions and their energetic costs. Combining actions with costs facilitates both higher-level planning (e.g., choosing an optimal running speed on a marathon) as well as planning on lower levels of an action hierarchy, such as determining the best movement trajectories for energy-efficient action. Recently, some of the findings on reported effects of effort on perception have been challenged as arising from task demands—participants guessing the purpose of the experimental manipulation and adjusting their estimates as a result. Arguably however, the failed replications used overly distracting cover stories which may have introduced task demands of their own, and masked other effects. The current study tested the generality of effects of potential effort on height and distance perception, employing effective yet not distracting cover stories. Four experiments attempted to identify conditions under which anticipated effort may systematically change perceptual estimates. Experiment 1 found that height estimates were not influenced by the effort required to place objects of different weights onto surfaces of varying heights. Experiments 2, 3 used two different effort manipulations (walking vs. hopping; and carrying an empty vs. a heavy backpack, respectively) and found that these did not influence estimates of distance (to be) traveled. Experiment 4 also used backpack weight to manipulate effort but critically, unlike Exp. 1–3 it did not employ a cover story and participants did not traverse distances after giving estimates. In contrast with the first three experiments, distances in the final experiment were estimated as longer when participants were encumbered by a backpack. Combined, these results suggest that the measured effects on the estimation of distance were due to how participants construed the task rather than being of a perceptual nature.